The Incidence of Node-Positive Non-small-Cell Lung Cancer Undergoing Sublobar Resection and the Role of Radiation in Its Management - Varlotto, John M.; Emmerick, Isabel; Voland, Rick; DeCamp, Malcom M.; Flickinger, John C.; Maddox, Debra J.; Herbert, Christine; Griffin, Molly; Rava, Paul; Fitzgerald, Thomas J.; Oliveira, Paulo; Baima, Jennifer; et al. (Frontiers in Oncology, 2020)
Purpose To identify the incidence, pre-operative risk factors, and prognosis associated with positive lymph node involvement(PLN) in patients undergoing a sub-lobar resection. Methods This is a retrospective study using the NCDB from 2004-2014 analyzing sub-lobar resections excluding those with any pre-operative chemotherapy and/or radiation, follow-up < 3 months, stage IV disease or >1 tumor nodule. Multi-variable modeling (MVA) was used to determine factors associated with overall survival (OS). Propensity score matching (PSM) was used to determine pre-operative risk factors for PLN in patients having at least one node examined and to assess radiation’s effect on OS in those patients with PLN. Result 40,202 individuals patients underwent sub-lobar resection, but only 58.3% had one lymph node examined. 2,615 individuals had PLN. PLN incidence decreased progressively from 15.1% in 2004 to 8.9% in 2014 (N1 6.3-3.0% and N2 8.4-5.9%). A lower risk of PLN was noted for squamous cell carcinomas, bronchioloalveolar (minimally invasive) adenocarcinomas, and right upper lobe locations. In the node positive group, OS was worse with not receiving chemotherapy or radiation. Radiation was associated with a strong trend for OS in entire node positive group (p= 0.0647) which was largely due to the effects on those having N2 disease (p =0.009) or R1 resections ( P= 0.03), but not N1 involvement( p = 0.87). Conclusion PLN incidence in sub-lobar resections has decreased overtime. Radiation appears to improve the OS in patients undergoing sub-lobar resection with nodal positivity, especially in those with N2 Nodal involvement and